Contemporary Review on Craniectomy and Cranioplasty; Part 2: Material Selection and Plate Manufacture. Issue 3 (29th May 2022) - Hatamleh, Muhanad M.
Abstract : Abstract: Cranioplasty materials include metals (ie, titanium); ceramics (ie, hydroxyapatite); polymers (ie, poly-methyl-metha-acrylate [PMMA]); and plastics (ie, polyether ether ketone). This paper aims to review their advantages and drawbacks. No ideal material currently exist, however, titanium implants are universally agreed to have lower infection rates than those reported for hydroxyapatite and PMMA implants; thus justifying their current wide use. These implants can be manufactured conventionally from medical grade titanium alloy Ti64 (titanium-aluminum-vanadium) in the form of plates ranging in thickness from 0.5 to 0.7 mm thick, or following the computer-aided design/manufacture principle. Surface finish of these implants is best achieved by electroplating.